โปรแกรมการตายของเซลล์ในแมลง - มานะบุญ มนพร (Science Essence Journal, 2011)
บทคัดย่อ โปรแกรมการตายของเซลล์เป็นเหตุการณ์ที่จำเป็นสำหรับการเจริญพัฒนาที่ปกติในสัตว์รวมทั้งแมลง ในแมลงที่มีการถอดรูปสมบูรณ์แบบแสดงให้เห็นว่าฮอร์โมนสเตอรอยด์ที่ชื่อ 20-ไฮดรอกซีเอคไดโซนเป็นตัวกระตุ้นให้เนื้อเยื่อของตัวหนอนสลายไปในระหว่างที่มีการถอดรูป ในสัตว์มีกระดูกสันหลังการควบคุมการตายอยู่ภายใต้การกระตุ้นของฮอร์โมนสเตียรอยด์เช่นเดียวกัน ดังนั้นกลไกในการกระตุ้นการทำงานของ 20-ไฮดรอกซีเอคไดโซนจึงเหมือนกับการควบคุมการตายที่พบในสัตว์มีกระดูกสันหลัง นั่นคือฮอร์โมนเอคไดโซนจะจับกับนิวเคลียร์รีเซบเตอร์ (nuclear receptor) คือ เอคไดโซนรีเซบเตอร์และอัลตราสไปราเคิล (EcR/Usp) เมื่อปริมาณฮอร์โมนเอคไดโซนในฮีโม-ลิมพ์เพิ่มสูงขึ้นจะไปมีผลกระตุ้นให้กลไกของฮอร์โมนเริ่มขึ้น บทบาทของฮอร์โมน 20-ไฮดรอกซีเอคไดโซนต่อการควบคุมการตายเกิดโดยการกระตุ้นผ่านยีน 2 ขั้นตอน คือ ขั้นแรกไปมีผลกระตุ้นการแสดงออกของยีนชุดแรก คือ early gene ซึ่งได้แก่ BR-C E73 และ E93 และ ขั้นที่ 2 คือ early gene จะส่งสัญญาณไปยังยีนอีกกลุ่มที่เกี่ยวข้องกับการตาย (death gene) ยีนในกลุ่มที่ 2 นี้เรียกว่า late gene ผลของการกระตุ้นโดย early gene ทำให้เซลล์เกิดการสร้างโปรตีนที่เกี่ยวข้องกับการตาย เนื่องจากยีนในกลุ่มนี้จะชักนำให้เซลล์เกิดการสลายตัวอย่างรวดเร็วและเห็นความเสียหายของการตายชัดเจน ทำให้เซลล์ตายในที่สุด ตัวอย่างของ late gene ที่มีบทบาทสำคัญ ได้แก่ rpr, hid และ dronc นอกเหนือไปจากการควบคุมของยีนใน 2 ขั้นตอนแล้ว ยังพบว่าเอนไซม์ที่มีบทบาทสำคัญมากต่อการควบคุมการตายของเซลล์คือเอนไซม์แคสเปส งานวิจัยในปัจจุบันได้แสดงให้เห็นว่ากลไกควบคุมการตายมีเอนไซม์นี้เป็นตัวกลางในการส่งสัญญาณระดับเซลล์ และพบว่ากลไกที่มีเอนไซม์แคสเปสเป็นตัวกลางนี้เหมือนกันกับที่พบในหนอนตัวกลม แมลงหวี่และมนุษย์ ดังนั้นความรู้ที่ได้จากการศึกษาเรื่องโปรแกรมการตายของเซลล์ในแมลงจึงถูกนำไปประยุกต์ใช้กับการศึกษาเรื่องโรคต่างๆ ในมนุษย์ที่เกิดเนื่องมาจากการเสื่อมสภาพหรือการตายของเซลล์ เช่น โรคอัลไซเมอร์ โรคพาร์คินสัน และโรคความผิดปกติของหัวใจ ABSTRACT Programmed cell death (PCD) is an essential event for normal development in animals including insects. In holometabolous insects, they have shown that the insect steroid hormone 20-hydroxyecdysone (20E) triggers cell death of larval specific tissues during metamorphosis. This regulation of cell death in insects and vertebrates are parallel because they are under the control of steroid hormones. Like vertebrate steroid hormone functions, ecdysone exerts its effects via steroid hormone receptor. In insects, the steroid hormone receptor for ecdysone is ecdysone receptor (EcR). EcR is a heterodimer of two nuclear receptors, EcR and Ultraspiracle (USP). The mechanisms regulating apoptosis in insects are initiated by an increasing in hemolymph ecdysteroid titer. The role of 20E to degenerate larval tissues is the activation of 20E through a two-step regulatory hierarchy of genes, primary-response genes or early genes and secondary-response target genes or late genes. In the beginning, the ecdysone/EcR/Usp complex directly regulates the early genes expression at a transcriptional level while late genes are important for death protein synthesis. The early genes include the BR-C E73 and E93, and the late genes are a set of genes which were activated by early genes. The late genes, rpr, hid and dronc, are death activator genes because they induce a rapid and massive destruction in the death cells. In addition to the activation of 20E on signal transduction pathway of early genes and late genes on programmed cell death, members of a family protease known as caspases comprise the core of apoptosis cell death. Recent researches reveal that the signaling pathway of programmed cell death mediated by caspase is similar among roundworms, insects and human. Hence, the knowledge obtained from the study of signal transduction pathway controlling programmed cell death in insects has been implied to the study of various human diseases caused by the degeneration of tissues or death of cells, such as Alzheimer’s , Parkinson’s and congenital heart disorder (CHD).